2019
DOI: 10.1002/jcop.22225
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem, cultural identification, and substance use among American Indian youth

Abstract: Objectives Determine potential mediating and moderating effects of self‐esteem on the relationship between cultural identification and substance use among American Indian (AI) youth. Methods Anonymous surveys were administered to middle and high school AI students assessing levels of last month alcohol and marijuana use, cultural identification, and self‐esteem. Structural equation modeling assessed potential mediating and moderating effects of self‐esteem on the relationship between AI and white identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Ethnic identity, the degree to which one identifies with a particular ethnicity/culture, does not show a strong relation to substance use, including alcohol, among AI youth (Bates, Beauvais, & Trimble, 1997;Dieterich, Stanley, Swaim, & Beauvais, 2013;Galliher, Jones, & Dahl, 2011;Swaim & Stanley, 2018a;Urbaeva, Booth, & Wei, 2017). However, several studies have found that reasons to drink may be different across countries and cultures (Kuntsche et al, 2015;Mackinnon et al, 2017), suggesting that ethnicity and identity may relate to motives for use.…”
Section: Ethnic Identitymentioning
confidence: 99%
“…Ethnic identity, the degree to which one identifies with a particular ethnicity/culture, does not show a strong relation to substance use, including alcohol, among AI youth (Bates, Beauvais, & Trimble, 1997;Dieterich, Stanley, Swaim, & Beauvais, 2013;Galliher, Jones, & Dahl, 2011;Swaim & Stanley, 2018a;Urbaeva, Booth, & Wei, 2017). However, several studies have found that reasons to drink may be different across countries and cultures (Kuntsche et al, 2015;Mackinnon et al, 2017), suggesting that ethnicity and identity may relate to motives for use.…”
Section: Ethnic Identitymentioning
confidence: 99%
“…son más comunes entre los adolescentes con baja autoestima 16,17,18,19,20,21,22,23,24,25,26,27,28 , asimismo, algunas investigaciones han referido una asociación entre una autoestima relativamente baja y el inicio del consumo de cannabis 29,30,31,32,33,34,35,36 . Sin embargo, aunque la aceptación de la autoestima como uno de los elementos críticos que afectan la elección y acción de comportamiento en el futuro 36,37 , algunas investigaciones han informado una asociación débil entre la autoestima y el consumo de cannabis 25,38,39 .…”
Section: Introductionunclassified
“…People with low self-esteem often feel inferior, depressed, desperate, and even suffer from mental illness ( 28 ). In addition, individuals with low self-esteem tend to use the substance to meet their self-esteem needs, thereby controlling their emotions ( 29 ). However, positive psychological capital, such as self-esteem, is an effective protective factor against substance dependence ( 30 ).…”
Section: Introductionmentioning
confidence: 99%